2016
DOI: 10.1007/s00425-016-2543-1
|View full text |Cite
|
Sign up to set email alerts
|

Three-way interaction among plants, bacteria, and coleopteran insects

Abstract: Main conclusionColeoptera, the largest and the most diverse Insecta order, is characterized by multiple adaptations to plant feeding. Insect-associated microorganisms can be important mediators and modulators of interactions between insects and plants.Interactions between plants and insects are highly complex and involve multiple factors. There are various defense mechanisms initiated by plants upon attack by herbivorous insects, including the development of morphological structures and the synthesis of toxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 222 publications
(240 reference statements)
0
47
0
Order By: Relevance
“…Plant-insect-microbe interactions can be classified into two categories: microbial mediation of plant-insect interactions and insect mediation of plant-microbe interactions (Pineda et al, 2010, 2013; Biere and Bennett, 2013; Fu and Dong, 2013; Pangesti et al, 2013; Lazebnik et al, 2014; Sugio et al, 2015). Microbes influence plant-insect interactions by suppressing or enhancing infestation of the plant by herbivores.…”
Section: Introductionmentioning
confidence: 99%
“…Plant-insect-microbe interactions can be classified into two categories: microbial mediation of plant-insect interactions and insect mediation of plant-microbe interactions (Pineda et al, 2010, 2013; Biere and Bennett, 2013; Fu and Dong, 2013; Pangesti et al, 2013; Lazebnik et al, 2014; Sugio et al, 2015). Microbes influence plant-insect interactions by suppressing or enhancing infestation of the plant by herbivores.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of thinking in terms of a holobiont organism is seen in the literature of plant herbivory and the "three-way interaction" (Wielkopolan & Obrępalska-Stęplowska, 2016) among plants, insects, and bacteria (Hammer & Bowers, 2015). Here the plant holobiont includes the eukaryotic plant cells and their bacteria, which collectively synthesize poisons against the insects and can signal predatory wasps to kill the herbivorous invaders.…”
Section: Scaffolded By Symbionts: Herbivorymentioning
confidence: 99%
“…Some of these symbiont microorganisms are mutualistic and contribute to the viability of their hosts, while others are parasites, which tend to affect their corresponding hosts in a negative way. Insect-associated microorganisms could be important mediators of interactions between insects and plants (Sugio, Dubreuil, Giron, & Simon, 2015;Hammer & Bowers, 2015, Wielkopolan & Obrępalska-Stęplowska, 2016. Some researchers have reported that simultaneous infection with different species of endosymbionts in the same host organism is a common phenomenon in several insect groups (Thao et al, 2000;Thao, Gullan, & Baumann, 2002;Russell et al, 2003;Ishii, Matsuura, Kakizawa, Nikoh, & Fukatsu, 2013;Krawczyk et al, 2015;El-Sayed et al, 2015;Ghosh, Bouvaine, & Maruthi, 2015;Brentassi et al, 2017).…”
Section: The Induction Mechanism Of Plant Galls By Insects: What Do Wmentioning
confidence: 99%